Pengelolaan Dana Desa untuk Pemberdayaan Masyarakat dalam Perspektif Ekonomi Islam: Penelitian - Wiharyono, Ade; Fasiri, Mawar Jannati Al; Syarief, Ghilman Nursidin (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The Village Fund is a crucial national program to accelerate development and enhance village independence, including in Wilulang Village, which is required to manage the 2025 Village Fund effectively, transparently, and in accordance with Islamic economic principles. This study aims to analyze the management of the Village Fund in community empowerment and assess its compliance with sharia values. Qualitative methods were used through interviews, observation, and documentation. The results indicate that the management of the Village Fund has followed the planning and monitoring stages, although community understanding of village finances remains limited. Various empowerment efforts, such as training, assistance with production equipment, and institutional strengthening, have been implemented, but these have not yet fully increased community independence. From an Islamic economic perspective, fund management in Wilulang reflects trustworthiness, justice, and welfare. Overall, the Village Fund has had a positive impact, but improvements in effectiveness, transparency, and community participation are still needed.